2017
DOI: 10.1073/pnas.1707727114
|View full text |Cite
|
Sign up to set email alerts
|

Coevolutionary arms race versus host defense chase in a tropical herbivore–plant system

Abstract: Coevolutionary models suggest that herbivores drive diversification and community composition in plants. For herbivores, many questions remain regarding how plant defenses shape host choice and community structure. We addressed these questions using the tree genus and its lepidopteran herbivores in the Amazon. We constructed phylogenies for both plants and insects and quantified host associations and plant defenses. We found that similarity in herbivore assemblages between species was correlated with similarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
142
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 132 publications
(154 citation statements)
references
References 89 publications
9
142
2
1
Order By: Relevance
“…The strong phylogenetic signal for tyrosine overexpression differs from the patterns seen for Inga secondary metabolites (Endara et al, , ; Kursar et al, ). Previously we have argued that herbivores have selected for divergent defences, such that close relatives are not more similar in secondary metabolites (Coley et al, ).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The strong phylogenetic signal for tyrosine overexpression differs from the patterns seen for Inga secondary metabolites (Endara et al, , ; Kursar et al, ). Previously we have argued that herbivores have selected for divergent defences, such that close relatives are not more similar in secondary metabolites (Coley et al, ).…”
Section: Discussionmentioning
confidence: 86%
“…In contrast, Noctuidae tend to avoid hosts that contain tyrosine, but are overrepresented on Inga with tyrosine‐ and tyramine‐gallates (Figure ). Our previous studies on Inga in Peru showed that the presence of tyrosine derivatives was among the most important factors for host selection by Noctuidae (Endara et al, ). In the present study, with a larger dataset, we show that this pattern extends to their entire regional distribution (Panama, Guiana Shield and Amazonia).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarity in herbivore communities among plant species is often correlated with similarity in defences rather than with plant phylogeny, so host selection by herbivores appears to be more evolutionarily constrained (Endara et al, 2017). For example, studies show that plant anti-herbivore traits are more or less independent of phylogeny and, thus, are evolutionarily labile, with frequent shifts in defence strategies as plants colonize new habitats.…”
Section: Future Promises and Challengesmentioning
confidence: 99%
“…The regulation of the adaptive response of the plant must be finely balanced between defence and acquisition of benefits (Giron et al, 2013;Endara et al, 2017). However, plants have to interact with multiple biotic partners ranging from parasites to mutualists.…”
Section: Introductionmentioning
confidence: 99%